2001
DOI: 10.1063/1.1403694
|View full text |Cite
|
Sign up to set email alerts
|

Temperature evolution of the translational density of states of liquid water

Abstract: The influence of temperature and density functional models in ab initio molecular dynamics simulation of liquid waterThe molecular dynamics technique is used to study the relative dynamics of tagged pairs of molecules and to derive the related translational density of states ͑DOS͒ of liquid water at 243, 273, and 373 K. The modes that compose the short-time dynamics of centers of mass are obtained. The dynamical quantities studied are characterized by a fast-time decay followed by a plateau whose height increa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

2002
2002
2004
2004

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 21 publications
0
5
0
Order By: Relevance
“…The same bands compose the DOS of liquid water. 12 The comparison argon-water over the reduced frequency scale shows that the main DOS difference is due to the intensities of the two bands. The longitudinal dynamics of neighbor particles of the two fluids is similar: the hindrance of the cage in a LJ system corresponds to the HB action in water, the cage being formed by the four H-bonded first neighbors.…”
Section: Dario Roccamentioning
confidence: 99%
See 1 more Smart Citation
“…The same bands compose the DOS of liquid water. 12 The comparison argon-water over the reduced frequency scale shows that the main DOS difference is due to the intensities of the two bands. The longitudinal dynamics of neighbor particles of the two fluids is similar: the hindrance of the cage in a LJ system corresponds to the HB action in water, the cage being formed by the four H-bonded first neighbors.…”
Section: Dario Roccamentioning
confidence: 99%
“…These results can be extended to the supercooled and melting liquids of argon and water, since the same three bands compose the total DOS of the two liquids. 11,12 The association of the 60 cm Ϫ1 band with the transverse dynamics was performed via a density current approach 14 16 or that the structural defects of the HB network, e.g., the bifurcated H bonds, 15 give spectral contributions near 60 cm Ϫ1 . Beyond these details, one can conclude that ͑a͒ the two bands that in water fall at about 60 cm Ϫ1 and 240 cm Ϫ1 are also present in argon liquid at the melting and supercooled states.…”
Section: Dario Roccamentioning
confidence: 99%
“…A detailed analysis of the static and dynamical properties of water via g(r,⍀ 1 ,⍀ 2 ) was performed elsewhere. 17,18 To obtain the time correlation functions ⌬B 19 and the VCF, molecular dynamics simulations at NVE conditions were carried out for 864 molecules interacting via the TIP4P potential 20 in a cubic box with periodic boundary conditions. The configurations of the liquid at the triple point (Tϭ273 K, ϭ1.0 g/cm 3 ) ͑melting state for simplicity͒ and of the supercooled state (Tϭ245 K, ϭ1.0 g/cm 3 ) were produced.…”
Section: ͑5͒mentioning
confidence: 99%
“…The evidence of a DOS excess is obtained by comparing the behaviour of disordered, crystalline and Debye-like systems, while the boson peak connection is suggested by the time decrease of the low-frequency mode intensity and by its disappearance when the crystallization process is over. These results are obtained by applying a methodology proposed for supercooled water states [20] and recently extended to normal liquid states [21].…”
mentioning
confidence: 99%
“…The term DOS is used to indicate the power spectrum of ω B(r 0 ; t) that yields part of the total DOS defined as the cosine Fourier transform of the velocity autocorrelation function[21] 5. It can be shown that this is true in the cases of water[21] and argon[22] liquid.…”
mentioning
confidence: 99%